(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research aims to investigate the evolution of digital marketing strategies for Small and Medium Enterprises (SMEs), with a focus on the use of social media and e-commerce. The research method used involves searching and evaluating relevant literature using reputable international databases, applying the PRISMA method to organize a systematic search and article selection process. The research results highlight the importance of innovation in business models, use of technology and data, and risk management in the context of digital marketing for SMEs. The implication of this research is to provide valuable insights for business practitioners and related stakeholders in developing more effective and adaptive digital marketing strategies for SMEs.